1967
DOI: 10.1099/00221287-47-3-325
|View full text |Cite
|
Sign up to set email alerts
|

Death Mechanisms in Airborne Escherichia coli

Abstract: SUMMARYDifferences in survival of Escherichia coli (strain B) sprayed from distilled water into air and into nitrogen as a function of relative humidity (RH) are reported. Two mechanisms which may contribute to death of airborne bacteria are described. In air one death mechanism occurring at low RH is attributed to the action of oxygen causing damage to flavin-linked enzymes as a result of free radical activity. Free radical suppressors are therefore expected to protect airborne E. coli B. Also, electron trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

1969
1969
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 10 publications
1
42
0
Order By: Relevance
“…Oxygen is known to be toxic to many bacterial aerosols, but often the effect may only be apparent at low r.h. (Hess, 1965;Cox, 1966;Benbough, 1967Benbough, , 1969Webb, 1967); it is possible that the poorer survival of L. pneumophila in drier air may be due in part to oxygen toxicity. One disadvantage of assessing microbial aerosol stability at only three representative r.h. values is that for many bacteria zones of relative instability exist at certain r.h. values (Anderson, 1966;Benbough, 1967;Cox, 1966Cox, , 1969Cox, , 1971) and similar zones of instability have been found for freeze-dried bacteria (Bateman et al 1961;Dewald et al 1967). The survey of the viability of L. pneumophila 74/81 aerosols held for 15 min showed that this organism survives poorly at 55 % r.h. compared with its stability at r.h. values slightly above and below this (65 and 40 % respectively); this suggests that such zones of instability also exist for legionella.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen is known to be toxic to many bacterial aerosols, but often the effect may only be apparent at low r.h. (Hess, 1965;Cox, 1966;Benbough, 1967Benbough, , 1969Webb, 1967); it is possible that the poorer survival of L. pneumophila in drier air may be due in part to oxygen toxicity. One disadvantage of assessing microbial aerosol stability at only three representative r.h. values is that for many bacteria zones of relative instability exist at certain r.h. values (Anderson, 1966;Benbough, 1967;Cox, 1966Cox, , 1969Cox, , 1971) and similar zones of instability have been found for freeze-dried bacteria (Bateman et al 1961;Dewald et al 1967). The survey of the viability of L. pneumophila 74/81 aerosols held for 15 min showed that this organism survives poorly at 55 % r.h. compared with its stability at r.h. values slightly above and below this (65 and 40 % respectively); this suggests that such zones of instability also exist for legionella.…”
Section: Discussionmentioning
confidence: 99%
“…However, comparison of the oxygen effects on freeze-dried bacteria (Lion & Bergmann, 1961;Lion & Avi-Dor, 1963) with those on airborne bacteria and simulation of the aerosolized state by drying bacterial suspensions on filter membranes (Benbough, 1967) have been successful in attempts to elucidate the death mechanisms of airborne bacteria. In dried bacteria enzymes and/or coenzymes concerned with pyruvate degradation and with the reduction of tetrazolium salts were affected.…”
Section: Introductionmentioning
confidence: 99%
“…Escherichia coli (strains B, JEPP and COMMUNE) and Klebsiella aerogenes (H. 8) were either grown in a chemically defined medium (Benbough, 1967) or in a complex tryptone medium (Anderson, 1966).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial survival in aerosols depends on a number of factors including relative humidity, composition of the gaseous environment and the compositions of both spray and collecting fluids (Webb, 1960;Cox, 1966a, b ;Benbough, 1967;Cox & Baldwin, 1967). Comparatively little is known about the effect of aerosolization upon the integrity of bacterial walls and membranes.…”
Section: Introductionmentioning
confidence: 99%